Multi-disciplinary approach for the management of non-metastatic non-small cell lung cancer in the Middle East and Africa: Expert panel recommendations. (August 2021) - Göker, Erdem; Altwairgi, Abdullah; Al-Omair, Ameen; Tfayli, Arafat; Black, Edward; Elsayed, Hany; Selek, Ugur; Koegelenberg, Coenraad
Highlights: Lung cancer is a leading cause of cancer related deaths globally and in MEA. Surgery remains a gold standard for treatment of resectable NSCLC. Other treatment modalities include chemotherapy, radiotherapy, targeted therapy and immunotherapy. We recommend use of MDT with a set composition for management of NSCLC in MEA. Abstract: The Middle East and Africa (MEA) region, a large geographical area, lies at the confluence of Asian, Caucasian and African races and comprises of a population with several distinct ethnicities. The course of management of non-small cell lung cancer (NSCLC) differs as per patients' performance status as well as stage of disease, requiring personalized therapy decisions. Although management of NSCLC has received a significant impetus in the form of molecularly targeted therapies and immune therapies in last few years, surgery remains gold standard for patients with early-stage disease. In case of unresectable disease, radiotherapy and chemotherapy are the primary management modalities. With newer therapies being approved for treatment of early stage disease, use of multi-disciplinary team (MDT) for comprehensive management of NSCLC is of prime importance. A group of experts with interest in thoracic oncology, deliberated and arrived at a consensus statement for the community oncologists treating patients with NSCLC in the MEA region. The deliberation was based on the review of the published evidence including literature and global and local guidelines, subject expertise of the participating panellists and experience in real-life management of patients with NSCLC. We present the proposed regional adaptations of international guidelines and recommends the MDT approach for management of NSCLC in MEA.